Micromorphological Studies of the Genus Ipomoea L. (Convolvulaceae) in Nepal - Shrestha, Saugat; Shrestha, Nawal; Rajbhandary, Sangeeta (Himalayan Biodiversity, 2017)
Ipomoea is a large and complex genus, which comprises the largest number of species within the family Convolvulaceae. Globally, the genus consists of about 600 species of vines and shrubs, which are widely distributed throughout the tropics and the subtropics. In Nepal, the genus comprises 15 species, which are distributed throughout the tropical, subtropical and temperate region of the country. Besides few enumerations and floristic surveys, no comprehensive anatomy and pollen characters of 16 species of Ipomoea occurring in Nepal to evaluate the qualitative and quantitative differences in these characters. We found that the all species of Ipomoea have paracytic type stomata. However, there is considerable variation in the size and frequency of the stomata. The size and shape of the epidermal cells also varies from species to species. Ipomoea nil has the highest stomatal frequency, while I. purpurea has the lowest frequency. All species of Ipomoea have globose, isopolar, echinate, pentoporate and radially symmetrical pollen grains. I. quamoclit has the largest pollen, while I. aquatica has the smallest pollen. The anatomy of stem shows no distinct structural differences among species. Although no qualitative differences in the studied characters are found among species, there is considerable variation in the quantitative characters, such as the size of stomata, frequency of stomata and pollen size. These characters could have important taxonomic and ecological implications and therefore, are as valuable as the morphological characters.